Roadmap for mainstreaming integrated pest management (IPM) into a climate smart one-health (CS-OH) framework - Tonnang, H.E.Z.; Tepa-Yotto, G.; Sokame, B.M.; Winsou, J.K.; Tamò, Manuele; Djouaka, R.F. (Elsevier, 2025)
Climate change presents significant challenges to agricultural sustainability, particularly in integrated pest management (IPM). To address these challenges, we propose a holistic and interdisciplinary conceptual framework, climate-smart One-Health (CS-OH), which integrates ecological, environmental, and socio-economic factors, considering human, animal, soil, and water health within the environment. This paper introduces a roadmap for Climate-Smart OH IPM, combining One-Health (OH) principles with climate-smart agriculture to promote sustainable pest management amid climate change. The roadmap utilizes Systems Thinking (ST) & System Dynamics (SD) methodologies to comprehend complex interactions in climate-affected agricultural systems. Additionally, we provide a step-by-step implementation of Digital Twin (DT) IPM, employing virtual models and real-time data for dynamic pest management. The roadmap's significance lies in optimizing resource allocation, fostering biodiversity, mitigating climate impact, and preventing zoonotic diseases. Furthermore, promoting adaptive pest management practices enhances agricultural system resilience. Through adopting this transformative roadmap, stakeholders can actively contribute to sustainable pest management and foster a healthier world for all.